Pola Baru Ekspansi Perizinan Perkebunan Kelapa Sawit Akses dan Relasi Kuasa Dalam Kawasan Hutan Di Indonesia - Sani Nur Asih (Institut Agama Islam Negeri (IAIN) Metro, 2023)
Indonesia is one of the largest contributors to palm oil in the world. Palm oil is one of the leading commodities that supports the running of the national economy in Indonesia. The high influence of palm oil economic growth in Indonesia has caused a shift in the cultivation of rubber and other conventional cash crops at the community level, turning into palm oil regardless of the role of palm oil for the nation's economy. The oil palm plantation industry is not welcomed by the Indonesian people, this is because the practice of oil palm plantations in Indonesia is suspected to be one of the triggers for various environmental and social problems, such as deforestation, peatland clearing, forest fires, biodiversity loss, and tenure conflicts. The total area of Indonesia's oil palm plantations is around 16.8 million hectares, of which about 3.47 million hectares are located in forest areas. The expansion of the palm oil industry in forest areas is partly due to the granting of oil palm plantation licensing authority to local governments, which is annulled as a trigger for new land clearing for oil palm plantations in the region. Without an accountable and strict control system in the licensing process, it will have an impact on the number of oil palm plantation permits issued that tend to violate many spatial planning requirements. In addition, further regulation of palm oil policies in the job creation law will actually increase the length of the conflict that occurs and make the process of improving palm oil governance much more complicated. The application of the